(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
In this article, the positive results of the family obtained on the basis of cross-breeding of largeskinned ridges and varieties belonging to the type of G.barbadense L. were noted. In particular, the most positive result for the period of 50% pod opening was observed in the population Family-19/1, which showed that the model was 4.0 days earlier than the variety Surkhan-14. In addition, a positive result on the location of the first harvest branch was determined in the population of Family-19/1 (3.9±0.23), and it was found that the model was superior to the variety Surkhan-14 by 0.6 difference (4.5±0.22).